Spirochaetosis of the human rectum associated with an intraepithelial mast cell and IgE plasma cell response. Issue 5 (May 1987) - Gebbers, J O; Ferguson, D J; Mason, C; Kelly, P; Jewell, D P
Abstract : In two patients presenting with mild intestinal symptoms, rectal spirochaetosis was the only morphological abnormality diagnosed by light microscopy. A re-evaluation of the morphological changes using electron microscopy and immunohistochemistry showed certain unusual features: the microorganisms were observed within epithelial cells and in subepithelial macrophages; there were numerous partially degranulated intraepithelial mast cells; and there was a marked increase in the proportion of IgE plasma cells within the lamina propria. Mucosal penetration by the organisms may be responsible for the unusual immune response. In one patient, treatment with antibiotics eliminated the spirochaetes and resulted in a clinical improvement. Spirochaetes should not always be considered as harmless commensals in the colon.